Clinical Presentations of Child Abuse: The Warning Signs in Medical Consultations in Some Referral Hospitals in Yaound. - Meguieze , Claude-Audrey; Haamit, Abba-Kabir; Nseme , Etouckey Eric; Voundi , Voundi Esther; Michle, Lowe Nantchouang Jacqueline; Rainatou, Ngapout; Isabelle, Mekone Nkwele; Paul, Koki Ndombo (European Journal of Health Sciences, 2022)
Purpose: The health practitioners must recognize both the warning signs of child abuse and collaborate in the prevention of its consequences. The general objective of this study was to report the different clinical presentations of abused children received in four referral hospitals in Yaound that could be used as warning signs in medical consultations. Methodology: A retrospective cross-sectional study was conducted in four referral hospitals in Yaound from January 1, 2015 to December 31, 2019. The target population of the study was children under the age of 18 who were victims of abuse. All records of children under 18 years who were victims of abuse were included in this study consecutively. The records were obtained from the archives of the hospitals. Statistical analysis was done using Epi-info TM version 7.2 software. Findings: Female children were the most frequently abused (121; 91.7%) with an age range of 0-14 years (125; 94.0%). The main reasons for medical consultation were the request for human immunodeficiency virus testing (105; 69.1%) and the suspicion of sexual assault (81; 53.3%). The most frequent traumatic lesions were lacerations (67; 59.3%) with the anogenital area (98; 86.7%) as the main body location. Conclusion: Improving the diagnosis of child abuse by studying clinical signs would be crucial in the fight against this scourge in our context by considering the infectious risk, the suspicion of sexual assault and anogenital lesions as the main warning signs. Recommendations: The study recommend campaigns to raise awareness on the issue of violence suffered by young girls, train health practitioners in psychological care and develop psychological monitoring.